Temporal Decline in Pathogen-Mediated Release of Methyl Salicylate Associated With Decreasing Vector Preference for Infected Over Uninfected Plants - Martini, Xavier; Coy, Monique; Kuhns, Emily; Stelinski, Lukasz L. (Frontiers in Ecology and Evolution, 2018)
The Asian citrus psyllid, Diaphorina citri Kuwayama, is the vector of the phytopathogenic bacterium, Candidatus Liberibacter asiaticus (CLas), that causes citrus greening. Diaphorina citri is attracted to methyl salicylate (MeSA) emitted by CLas-infected citrus. MeSA is catalyzed from salicylic acid (SA) by salicylic acid methyl transferase (SAMT). In addition, salicylate hydroxylase, an enzyme that degrades SA and suppresses host plant defense, is unregulated in CLas-infected as compared with uninfected citrus. Based on these findings, we hypothesized that CLas-induced plant volatile emissions and SAMT expression may decrease over time following CLas infection. We first identified the putative Citrus sinensis SAMT (CsSAMT) that methylates SA to MeSA. Thereafter we compared changes in SAMT expression and volatile expression between uninfected citrus, citrus recently (< 6 months) infected with CLas, and citrus infected with CLas for a long (>1 year) duration. Emission of MeSA increased in citrus recently infected with CLas, whereas both MeSA emissions and SAMT expression decreased in long-infected citrus as compared with uninfected controls. Also, there was a significant decrease in release of limonene from citrus infected >1 year, and a concomitant increase in release of β-caryophyllene in both recent and long-infected citrus as compared with controls. In behavioral assays, D. citri preferred settling on asymptomatic citrus recently infected with CLas over uninfected or long-infected citrus trees. The odor of citrus recently infected with CLas was more attractive to D. citri than the odor of uninfected or long-infected citrus. There was an association between the preference for citrus odor of recently infected plants and an increase of MeSA release following CLas infection. Overall, our study demonstrated pulsed changes in citrus odor release following CLas infection. We hypothesize that allocation of resources to plant defense in citrus decreases as a function of huanglongbing disease symptom progression. These changes affected the behavior of the CLas vector. Our study confirms previous reports demonstrating that plant defenses boosted following phytopatogen infection tend to decrease over time. Implications on the CLas epidemic are discussed.